2018
DOI: 10.1016/j.vaccine.2017.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of protection induced by immunisation of domestic pigs with deletion mutant African swine fever virus BeninΔMGF by different doses and routes

Abstract: HighlightsImmunised pigs with BeninΔMGF were protected against parental virulent ASFV strain.To improve safety and efficacy new doses and routes of immunisation were tested.Intramuscular immunisation of high doses showed the best percentage of protection.A new ELISA detected specific IgM antibodies at early stages after ASFV infection.Early induction of IFNγ and IL-10 in vaccinated pigs probably critical to protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 24 publications
4
64
0
Order By: Relevance
“…Similar to previous results (22,24), the virus genome was detected in blood samples from all animals immunized with BeninΔMGF (group B) at days 14, 24, and 52 p.i. Viremia levels decreased progressively from day 14 p.i.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Similar to previous results (22,24), the virus genome was detected in blood samples from all animals immunized with BeninΔMGF (group B) at days 14, 24, and 52 p.i. Viremia levels decreased progressively from day 14 p.i.…”
Section: Resultssupporting
confidence: 89%
“…Single immunizations with BeninΔMGF have not been tested before. However, even lower doses (10 2 and 10 3 TCID 50 ) administered twice by the intramuscular route over an interval of 3 weeks were able to induce up to 100% protection (22,24) when animals were challenged shortly (18 to 21 days) after the boost immunization. On the basis of these results and with the objective of performing a comparative evaluation, both vaccine candidates were selected to test in parallel their capacity to induce long-term protection after a single dose (10 4 TCID 50 ) was administered by the intramuscular route, considered the most feasible and safest route for immunizations.…”
Section: Importancementioning
confidence: 96%
See 1 more Smart Citation
“…A new generation of ASFV gene-deletion mutants have been generated that have induced protective responses in pigs ( O’Donnell et al, 2015a , Reis et al, 2016 , O’Donnell et al, 2017 , Monteagudo et al, 2017 , Sánchez-Cordón et al, 2017b ). Cross-protection against a genotype II isolate was induced by a genotype I attenuated virus, suggesting that cross-protective attenuated virus vaccines may be feasible.…”
Section: Development Of Vaccines Against African Swine Fever Virusmentioning
confidence: 99%
“…Having noted the drawbacks of in vitro attenuated ASFVs, target gene‐deleted live attenuated and subunit vaccines become attractive options, and as a result, several gene‐deleted ASF vaccines have been attempted (Gallardo, Sánchez, et al, ; Monteagudo et al, ; O’Donnell et al, , ; Reis et al, ). By targeted deletion of virulence‐related genes, it has been shown that it would be possible to define the balance between attenuation and immunogenicity (Reis et al, ; Sánchez‐Cordón, Jabbar, et al, ). To date, several virulence‐associated ASFV genes such as 9GL, UK, CD2v, DP148R and MGFs have been deleted to generate attenuated ASF vaccines.…”
Section: Asf Vaccine Strategies Have Evolved Through Different Scenariosmentioning
confidence: 99%